COVID-19 INFECTION DURING PREGNANCY WITH ACUTE HEART FAILURE, VENOUS THROMBOSIS AND PNEUMONIA - Soofi, Muhammad Adil; Shah, Muhammad Azam; Mhish, Olaa Hassan; AlSamadi, Faisal (Journal of Ayub Medical College Abbottabad, 2022)
The COVID-19 infection has spread rampantly, attaining pandemic status within three months of its first appearance. It has been classically associated with respiratory signs and symptoms. However, unusual presentations have also been reported in multiple literatures. We are reporting a case of acute heart failure in a pregnant patient diagnosed with Covid-19 infection. Her hospital course has been complicated by pneumonia and venous thrombosis during the postpartum period. Her laboratory investigations showed evidence of myocardial injury, acute heart failure, and COVID-19 infection in second PCR sample taken during postpartum period. Echocardiography exhibited features of severe left ventricle systolic dysfunction. She had successful delivery through caesarean-section, nevertheless, her postpartum period was complicated by pneumonia and right femoral venous thrombosis. CT scan of the chest and pulmonary arteries revealed infiltrations in the left lower lobe and right middle lobe, suggestive of consolidation, with no evidence of pulmonary embolism. Cardiac MRI displayed severe global LV and RV systolic dysfunction, but no evidence of myocardial infarction, myocardial infiltration, or abnormal myocardial delayed enhancement. Her condition improved and she was discharged on heart failure medications. During follow-up at the heart failure clinic, her symptoms continued to ameliorate, except the LV and RV systolic dysfunction which persisted. Multiple unusual presentations of Covid-19 infection have been reported in various literatures and screening of the COVID-19 infection should be practiced on regular basis especially among high-risk patients. Prompt identification of COVID-19 infection will lead to proper isolation and mitigation of infection spread among hospitalized patients and health care workers. Covid-19 PCR should be repeated in cases having clinical indication and negative first sample. A proper history and cardiac MRI can differentiate between different aetiologies of heart failure during pregnancy and peripartum COVID-19 infection. Adequate anticoagulation should be considered in COVID-19 patients due to the high risk of thromboembolism. Among patients with COVID-19 infection, CT chest helps demonstrate the extent of pulmonary involvement.